The promotion mechanism of prebiotics for probiotics: A review - You, Siyong; Ma, Yuchen; Yan, Bowen; Pei, Wenhui; Wu, Qiming; Ding, Chao; Huang, Caoxing (Frontiers in Nutrition, 2022)
Prebiotics and probiotics play a positive role in promoting human nutrition and health. Prebiotics are compounds that cannot be digested by the host, but can be used and fermented by probiotics, so as to promote the reproduction and metabolism of intestinal probiotics for the health of body. It has been confirmed that probiotics have clinical or health care functions in preventing or controlling intestinal, respiratory, and urogenital infections, allergic reaction, inflammatory bowel disease, irritable bowel syndrome and other aspects. However, there are few systematic summaries of these types, mechanisms of action and the promotion relationship between prebiotics and probiotic. Therefore, we summarized the various types of prebiotics and probiotics, their individual action mechanisms, and the mechanism of prebiotics promoting probiotics in the intestinal tract. It is hoped this review can provide new ideas for the application of prebiotics and probiotics in the future.